ՀՀ հարկային և մաքսային մարմինների գործունեության թափանցիկության և հաշվետվողականության ապահովման ուղիները - Շուշան Սասունիկի Ասատրյան (ՀՀ ԳԱԱ հրատ.)
На современном этапе хозяйствования обеспечение прозрачности и подотчетности деятельности налоговых и таможенных органов является одной из важнейших задач государства, решение которой позволит сформировать конкурентоспособную и соотствующую нынешней ситуации налоговую и таможную системы. At the current stage of economic activities ensuring the transparency and accountability of the activities of tax and customs bodies and/or authorities is one of the most important objectives of the government, the and addressing these issues would allow forming a competitive tax and customs system in line with the current economic situation.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ